Which factors lead to frequent attendance in the outpatient sector among individuals in the second half of life? Evidence from a population-based longitudinal study in Germany - André Hajek; Hans-Helmut König (BMC, 2018)
Abstract Background Despite only constituting a small percentage of the population, frequent attenders place a tremendous burden on the healthcare system in Germany. Whilst there are some cross-sectional studies that examine the correlates of frequent attendance among older adults, there are only a few longitudinal studies that analyze the factors that lead to frequent attendance among middle-aged or older adults. Thus, the aim of this study was to investigate the factors leading to frequent attendance in the outpatient sector longitudinally. Methods Data was drawn from three waves of a large, population-based sample of community-dwelling individuals aged 40 and above in Germany (n = 1049 in fixed effects regression). Individuals were classified as frequent attenders (GP visits) if they had, on average, visited a GP every second month in the previous 12 months. The same logic was applied for specialist visits. Results Conditional FE logistic regressions showed that the onset of frequent attendance (GP visits) was negatively associated with age [OR: 0.91, 95% CI: 0.87-0.95], a change in employment status from employed to unemployed [OR: 2.26, 1.17-4.39], decreases in physical functioning [OR: 0.98, 0.97-0.99], worsening self-rated health [OR: 1.40, 1.11-1.78], and increases in physical illnesses [OR: 1.18, 1.06-1.32]. Similarly, the onset of frequent attendance (specialist visits) was associated with age [OR: 0.95, 0.92-0.98], decreases in physical functioning [OR: 0.99, 0.98-1.00], worsening self-rated health [OR: 1.50, 1.25-1.79], and increases in physical illnesses [OR: 1.24, 1.13-1.35]. Conclusions Need factors in particular were associated with the onset of frequent attendance. This relation did not vary by gender nor education, which may indicate that individuals only start to use health services more frequently when their needs increase.